Identification and molecular characterization of border disease virus (BDV) from sheep in India. (February 2016) - Mishra, Niranjan; Rajukumar, Katherukamem; Vilcek, Stefan; Kalaiyarasu, Semmannan; Behera, Sthita Pragnya; Dubey, Pooja; Nema, Ram Kumar; Gavade, Vishal Balbhim; Dubey, Shiv Chandra; Kulkarni, D.D.
Highlights: We detected border disease virus in sheep in India for the first time. Genetic and antigenic analysis reveals that the BDV isolated from sheep belongs to BDV-3 genotype. The origin of BDV in India may be through trade in sheep with the other countries or BDV-3 may be widely distributed. For BDV diagnosis, commercial BVDV antigen ELISA should be used with caution. Abstract: Pestiviruses isolated from sheep and goats in India thus far have been bovine viral diarrhoea virus 1 (BVDV-1) or BVDV-2. During routine genetic typing of pestiviruses in the years 2009-10, border disease virus (BDV) was detected in eight Indian sheep of a flock showing clinical signs of BD by real time RT-PCR. All the samples yielded positive virus isolates in cell culture but were found negative by a BVDV antigen ELISA. A representative BDV isolate was characterized at genetic and antigenic level. Phylogenetic analysis carried out in 5′-UTR, N pro and E2 regions of genome typed the Indian BDV isolate as BDV-3. A more detailed analysis in N pro and entire region coding structural proteins showed that the N pro (168), C (100 aa), E rns (227 aa), E1 (195 aa) and E2 (373 aa) proteins were of size characteristic for BDV reference strain X818. Antigenic differences were evident between the BDV-3 isolate and previously reported BDV-1, BDV-5 and BDV-7 strains. Although origin of BDV-3 in India is not clear, the results reflect probable introduction through trade in sheep between India and other countries or BDV-3 may be more widely distributed. Additionally, this study suggests that for diagnosis of BDV infection, the commercial BVDV Ag-ELISA should be used with caution. This is the first identification of BDV in sheep in India which highlights the need for continued pestivirus surveillance and assessing its impact on sheep and goat production.